The study and application of the IOT technology in agriculture - Ji-chun Zhao; Jun-feng Zhang; Yu Feng; Jian-xin Guo (2010 3rd IEEE International Conference on Computer Science and Information Technology, 2010)
In recent years, greenhouse technology in agriculture is to automation, information technology direction with the IOT (internet of things) technology rapid development and wide application. In the paper, control networks and information networks integration of IOT technology has been studied based on the actual situation of agricultural production. Remote monitoring system with internet and wireless communications combined is proposed. At the same time, taking into account the system, information management system is designed. The collected data by the system provided for agricultural research facilities.